Continuity and Succession of States: The Fate of Pre-War Germany and Its Implications for the 1970 Treaty of Warsaw (Polish Yearbook of International Law, 2023)
This article explores whether the Federal Republic of Germany (FRG) is identical with pre-war Germany. The question is relevant for the understanding ofthe 1970 Treaty of Warsaw, because in the event it is identical, the FRG would be the predecessor State of Poland with regard to the former German territories east of the Oder-Neisse line and, therefore, competent to renounce any territorial title. By contrast, in the case of non-identity the FRG would only have been a third State with regard to these territories. However, even in case of identity, the scope of the Treaty of Warsaw seems ambiguous due to Allied reservations. Hence, it was wise to confrm the transfer of sovereignty in 1990.